X-ray irradiation induces disruption of the blood–brain barrier with localized changes in claudin-5 and activation of microglia in the mouse brain. (October 2018) - Yoshida, Yukari; Sejimo, Yukihiko; Kurachi, Masashi; Ishizaki, Yasuki; Nakano, Takashi; Takahashi, Akihisa
Abstract: X-ray irradiation (X-irradiation) induces disruption of the blood–brain barrier (BBB). However, the mechanisms underlying the permeability changes are unclear. Therefore, in the present study, we examined the cellular and molecular changes produced by X-irradiation of the brain. Male ICR mice were irradiated locally on their head, posterior to the bregma, except for the eyes, with a single dose of 60 Gy. BBB permeability was assessed using Evans blue dye. We also examined vascular endothelial growth factor (VEGF) expression, microglial morphology, and the expression of the tight junction protein claudin-5 from 0.5 to 7 days after irradiation. An increase in BBB permeability and a decrease in the expression of VEGF protein occurred in a time-dependent manner. In addition, the number of activated microglia (CD68 + /Iba-1 + double-positive cells), the amount of tumor necrosis factor-α protein and immunoreactivity of nuclear factor-kappaB increased by irradiation, while the expression of claudin-5 on vascular endothelial cells diminished markedly in the cerebral cortex starting 0.5 days after irradiation. These results suggest that the downregulation of claudin-5 expression mediated by activated microglia may contribute to the BBB disruption induced by X-irradiation. Highlights: X-ray irradiation (X-irradiation) induces acute BBB disruption in the mouse brain. X-irradiation activates microglia in the mouse brain. X-irradiation induces the apoptosis of endothelial cells (ECs) and decreases ECs. X-irradiation induces tight junction (TJ) protein translocation in the mouse brain. X-irradiation increases tumor necrosis factor (TNF)-α and nuclear factor-kappaB (NF-κB) expression in the mouse brain.